Concept analysis: some limitations and possible solutions - Botes, A (Curationis (Pretoria), 2002)
Concepts are the basic building blocks of scientific knowledge or theoretical frameworks for any discipline. The strength of the theories that guide a discipline is dependent on the quality of the concept analysis. Thus, the utilisation of poorly understood concepts in research and theory development will result in questionable reliability and validity. Concept analysis is associated with the research design of philosophical inquiry. The purpose of philosophical inquiry is to perform research using intellectual analysis to clarify meaning. Traditionally, no empirical (qualitative or quantitative) investigations were used to clarify the meaning of concepts. The lack of empirical investigation to clarify concepts, results in certain limitations in the methodology of concept analysis. It seems that methodological innovations for enhancing concept analysis is urgently required. The purpose of this article is to describe the utilisation of qualitative and quantitative strategies with literature review in concept analysis as a possible solution to limitations. This article will firstly, describe the limitations in the traditional Wilsonian methods of concept analysis and will secondly demonstrate how the introduction of qualitative and quantitative methods with literature review can overcome some of the limitations. An example a research study on quality of life (Ferrans, 1997:110) will be used to demonstrate how qualitative and quantitative empirical methods with literature review can enhance the quality of concept analysis.